REPRESENTASI RUANG DAN TOKOH PELACUR DALAM PROSA INDONESIA MODERN - jatmiko, Dheny (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
This article discusses the representation of space and prostitute characters in Indonesian modern prose. The data were taken from Bumi Manusia, Kembang Jepun, Perempuan Kembang Jepun, Kremil, and Existere. The discussion aims at reconstructing prostitution in Surabaya and analyzing the prostitution related to the social, economic, and political problems. Bumi Manusia portrays a prostitution managed by a Chinese in the era of Dutch colonization. Kembang Jepun and Perempuan Kembang Jepun taken the colonial time and Japanese occupation as the setting of the novels describes the relationship between prostitution and political issues such as anti-colonial movements and independent struggle. In Kremil whose setting is 1960s, one can read the relationship between prostitution and the tragedy of PKI (Indonesian Communist Party). Existere portrays the prostitution in Dolly. Key words: Representasi, Sastra Bandingan, Pelacuran, Surabaya